Long‐Term Behavior of a Solid Oxide Electrolyzer (SOEC) Stack. Issue 6 (15th October 2020) - Lang, M.; Raab, S.; Lemcke, M. S.; Bohn, C.; Pysik, M.
Abstract: The successful market introduction of the solid oxide fuel/electrolysis cell technology for power‐to‐gas applications requires the reduction of the degradation rates and the better understanding of the degradation mechanisms of the stacks. Therefore, the paper reports and compares the long‐term behavior of a solid oxide cell stack in electrolysis and reversible fuel cell/electrolysis operation. The 30‐cell stack with electrolyte supported cells was supplied by Sunfire GmbH (Dresden/Germany) in the German funded RSOC Project. The stack was operated for 3, 370 h in electrolysis and afterwards for 2, 500 h in reversible fuel cell/electrolysis mode, each at 70% gas conversion. In the beginning of the test, the stack showed high gas tightness, good performances and high efficiencies in both SOEC and SOFC operations. During 3, 370 h of SOEC operation a low degradation of +0.5%/1, 000 h was measured. During 2, 500 h of reversible fuel cell/electrolysis cycling, the gas tightness of the stack slightly decreased, which led to a temperature increase, and higher degradation rates were observed. The increase of the ohmic resistance contributed mostly to the degradation. Optimized operating conditions for reversible cycling and increasing the purity of the supplied water are foreseen in order to minimize stack degradation in reversible operation.